2016
DOI: 10.1136/bmjopen-2016-012352
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of telehealth for patients with raised cardiovascular disease risk: evidence from the Healthlines randomised controlled trial

Abstract: ObjectivesTo investigate the cost-effectiveness of a telehealth intervention for primary care patients with raised cardiovascular disease (CVD) risk.DesignA prospective within-trial patient-level economic evaluation conducted alongside a randomised controlled trial.SettingPatients recruited through primary care, and intervention delivered via telehealth service.ParticipantsAdults with a 10-year CVD risk ≥20%, as measured by the QRISK2 algorithm, with at least 1 modifiable risk factor.InterventionA series of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…RM is cost-effective for managing chronic obstructive pulmonary disease and congestive heart failure, with emerging positive economic data in diabetes care, management of elevated cardiovascular risk, and perhaps even depression [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Cost-savings in these scenarios are driven by improved efficiencies in care and reduced complications.…”
Section: Discussionmentioning
confidence: 99%
“…RM is cost-effective for managing chronic obstructive pulmonary disease and congestive heart failure, with emerging positive economic data in diabetes care, management of elevated cardiovascular risk, and perhaps even depression [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Cost-savings in these scenarios are driven by improved efficiencies in care and reduced complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies in other disease states have shown cost-effectiveness of telehealth interventions, studies evaluating the impact of RPM in the dialysis population are needed to justify its widespread use. 43 , 44 …”
Section: Methodsmentioning
confidence: 99%
“…The methods used for multiple imputation are described in further detail in the companion 12-month economic evaluation paper. 12 …”
Section: Methodsmentioning
confidence: 99%
“…The long-term cost-effectiveness analysis complements the analysis of cost-effectiveness of the intervention at 12 months postrandomisation published in a companion paper. 12 …”
Section: Introductionmentioning
confidence: 99%